Cleaning of Public Cemeteries and the Recitation of Surah Yasin as Efforts to Preserve the Environment and Community Traditions - Moch. Hasan Sidqi; Iszanul Dani Nurdiansah; Hasmi Nur Bayhaqi; M. Yusron Maulana El-Yunusi; Didit Darmawan (Jurnal Pengabdian Masyarakat Al-Fatimah, 2024)
The environment is a crucial part of human life that must be preserved to create harmony between humans and nature. A team from Sunan Giri University Surabaya (UNSURI) conducted a community service activity in Tambak Lekok Village, focusing on the cleanliness of public cemeteries, often neglected public facilities. The activity, held on July 30-31, 2024, included cleaning the cemetery and the collective recitation of Surah Yasin. The method employed was Participatory Action Research (PAR), where the community was directly involved in the environmental cleaning process. The stages of the activity included initial observation of the cemetery’s condition, cleaning, and religious rituals. The results demonstrated an improvement in environmental cleanliness and a collective awareness among the community regarding the importance of maintaining cleanliness and ancestral traditions. Through active participation, this activity enhanced the quality of the environment and strengthened the spiritual and social values within the community of Tambak Lekok Village